2011
DOI: 10.1167/iovs.10-6098
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopic Evidence of Keratopathy in Patients with Pseudoexfoliation Syndrome

Abstract: These results have shed light on understanding of the pathogenesis of decreased corneal sensitivity in eyes with PEX syndrome. PEX syndrome is probably a binocular condition for which keratopathy of the fellow eye also requires observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
4
15

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 18 publications
8
50
4
15
Order By: Relevance
“…We found no significant difference in the mean basal epithelial cell density between groups 1 and 2 and between patients with PEX and healthy control subjects. This finding contradicts those of previous studies, which showed significant differences in the mean basal epithelial cell density between patients with PEX and healthy control subjects (3,4) .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We found no significant difference in the mean basal epithelial cell density between groups 1 and 2 and between patients with PEX and healthy control subjects. This finding contradicts those of previous studies, which showed significant differences in the mean basal epithelial cell density between patients with PEX and healthy control subjects (3,4) .…”
Section: Discussioncontrasting
confidence: 99%
“…In a prospective observational case series, Sbeity et al used noncontact in vivo corneal confocal microscopy to detect PEM on the lens surfaces and corneal endothelium of PEX eyes and their fellow eyes (8) . Moreover, Zheng et al demonstrated a decrease in corneal sensitivity as well as all of the corneal cell density and corneal sub-basal nerve plexus variables in patients with PEX (3) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations